Pressure Analysis in the Draft Tube of a Pump-Turbine under Steady and Transient Conditions - Jing Yang (Energies, 2021)
Pumped-storage power stations play a regulatory role in the power grid through frequent transition processes. The pressure pulsation in the draft tube of the pump-turbine under transient processes is important for safe operation, which is more intense than that in the steady-state condition. However, there is no effective method to obtain the exact pressure in the draft tube in the transient flow field. In this paper, the pressure in the draft tube of a pump-turbine under steady-state and transient conditions are studied by means of CFD. The reliability of the simulation method is verified by comparing the real pressure pulsation data with the test results. Due to the distribution of the pressure pulsation in the draft tube being complex and uneven, the location of the pressure monitoring points directly affects the accurate judgement of cavitation. Eight monitoring surfaces were set in the straight cone of the draft tube and nine monitoring points were set on each monitoring surface to analyze the pressure differences on the wall and inside the center of the draft tube. The relationships between the pressure pulsation value inside the center of the draft tube and on the wall are studied. The “critical” wall pressure pulsation value when cavitation occurs is obtained. This study provides references for judging cavitation occurrences by using the wall pressure pulsation value in practical engineering.